Breast cancer screening: Impact on care pathways. (6th June 2019) - Lefeuvre, Delphine; Catajar, Nathalie; Le Bihan Benjamin, Christine; Ifrah, Norbert; De Bels, Frédéric; Viguier, Jérôme; Bousquet, Philippe Jean
Abstract: Background: Controversy persists concerning screening programs (SPs), related to a potential risk of overdiagnosis or the impact on survival. One of the main questions to be addressed concerns the aggressiveness of the related treatments. Methods: Using the "Cancer Cohort, " a national‐based cohort (medico‐administrative database), all women between the ages of 50 and 74 years and treated in 2014 for incident breast cancer were compared, according to whether their diagnosis was made following a mammogram performed within the framework of the SP (SP group) or outside it (NSP group). Results: A total of 23 788 women were identified: 13 530 (57%) in the SP group and 10 258 (43%) in the NSP group. The women in the SP group had a higher rate of in situ or localized invasive breast cancer. They had a higher rate of breast‐conserving surgery (82% vs 70%), and a lower rate of chemotherapy (34% vs 53%). These findings were observed irrespective of the stage. They had a higher rate of pathways involving breast‐conserving surgery followed by radiotherapy. Among women with metastatic cancer, those in the SP group had a lower proportion of liver, lung, brain, and bone metastases, and a higher proportion of lymph node metastases (other than axillary), irrespective of the time to onset of the metastases. Conclusion: The women in whom cancer was diagnosed following a mammogram performed in the context of the SP had less advanced cancer and less aggressive treatments. This observational study helps illustrate the benefit of the SP in France using a different approach. Abstract : The women whose cancer was diagnosed following a mammogram carried out within the framework of the screening program had less advanced cancer and less aggressive treatments accordingly to the stage than the women diagnosed outside the screening group.